Redeemed by my forbidden housekeeper - Rice, Heidi (Harlequin presents, 2023)
""I did not want her here..." Recovering from a near-deadly accident, Renzo Camaro retreated to his C̥te D'Azur estate. Nothing breaks through his solitude. Until the arrival of his new housekeeper stirs dormant desires... "It was past time I moved on..." Jessie Burton took this job to get closure. Yet bitter and broken Renzo is changed from the playboy who gave her one eye-opening night then abruptly left. He still drives her wild with want! But unless she can forgive the pain he caused, Jessie must remain immune to their connection..."--Back cover.